Game-related skills that influence success in elite men`s Volleyball - Drikos, S.; Sotiropoulos, K.; Barzouka, K. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
Skills and complexes` effectiveness is crucial for elite-level male volleyball teams. This study investigated the importance of game-related skills in the Men`s European Championship 2021. The effectiveness of skills such as serve (SE), reception (RE), attack after reception (A1E), attack after defence (A2E), block (BE) and the success rates of each team in Complex 1 (SOwin) and Complex 2 (BPwin) were computed. Two stepwise discriminate analyses were performed to identify the contribution of each skill`s effectiveness and complex success rate to winning in a balanced volleyball set and to the team`s classification. Cross validations results showed that the discriminant function correctly classified 87.1% of the 334 teams` performance in win-lose sets and 75.0% of the teams` performance level. The variables which were central in defining discriminant dimension were BPwin = .530 and A1E = .328 for win-lose sets, as for performance levels were BPwin = .712, A1E = .618 and A2E = .408. The results of the study indicate that success in volleyball either in a balanced set or in a tournament can be explained with just two performance indicators: the effectiveness of attack after reception and the success rate of the Complex 2.